2010
DOI: 10.1074/jbc.m110.105544
|View full text |Cite
|
Sign up to set email alerts
|

WSS25 Inhibits Growth of Xenografted Hepatocellular Cancer Cells in Nude Mice by Disrupting Angiogenesis via Blocking Bone Morphogenetic Protein (BMP)/Smad/Id1 Signaling

Abstract: Hepatocellular cancer (HCC)3 is the fourth leading cause of death from cancer worldwide and the second most lethal malignant cancer in China since the 1990s (1). However, there are few treatment options aside from surgery (1). HCC is characterized by hypervascularity, which can distinguish HCC from benign lesions by angiography. The strategy of blocking angiogenesis in HCC to inhibit tumor growth has been used for more than 20 years in the clinic (2). However, there are no ideal antiangiogenesis chemotherapeut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 43 publications
0
41
0
Order By: Relevance
“…The effect on cell proliferation was determined using the MTT [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide] method [44].…”
Section: Anti-proliferative Activity Assaymentioning
confidence: 99%
“…The effect on cell proliferation was determined using the MTT [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide] method [44].…”
Section: Anti-proliferative Activity Assaymentioning
confidence: 99%
“…Wound Healing Recovery Assay (28,29)-MLECs (2 ϫ 10 5 cells per well) were seeded into a six-well plate and reached confluency after culture for 24 h. A wound gap was made by scratching with a T-200 tip in each well. After removing debris by PBS washing, the cells were cultured in DMEM medium supplemented with 10% FBS.…”
Section: Methodsmentioning
confidence: 99%
“…Cell Proliferation Assay (28,29)-Ext1f/f or Ext1Ϫ/Ϫ MLECs (3000 cells/well) were seeded into a 96-well plate. Cell growth was assessed by colorimetric assay using the Cell Counting Kit-8 kit (Dojindo Molecular Technologies, Santa Clara, CA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study in our lab demonstrated that WSS25 binds to BMP-2 and that its receptors inhibited xenografted hepatocellular cancer cell growth and disrupted angiogenesis [26][27][28] . As we mentioned above, BMP-2 is also a crucial factor in bone remodeling.…”
Section: Introductionmentioning
confidence: 99%